Case report: Robotically visualized and biopsy-confirmed peritoneal carcinomatosis as initial identification of metastatic prostate adenocarcinoma in a patient with a history of prostatic urethral lift - Khan, Qateeb; Myers, Bryn; Bowar, Breann; Khan, Maryam; Mullaney, Henry; Gainey, Jordan; Schneider, Robert; Dahmoush, Laila; Nepple, Kenneth G.; Byrne, James D. (Frontiers in Oncology, 2024)
Background: Peritoneal carcinomatosis is a particularly rare presentation of prostate cancer. Here we report a rare clinical case of surgically identified peritoneal carcinomatosis at the time of planned robotic prostatectomy in patient with a history of prostatic urethral lift procedure.Case Presentation: A 72-year-old male, with history of urinary retention managed with tamsulosin, presented to his local urologist. Prostatic urethral lift procedures were performed for symptom management. After a definitive uptrend in his PSA values, a biopsy was obtained that demonstrated prostate adenocarcinoma. On presurgical multidisciplinary review, it was presumed he had very high-risk localized prostate cancer. However, upon initiation of robotically assisted laparoscopic radical prostatectomy (RALP) he was noted to have numerous punctate white plaques on the peritoneum; biopsy of these lesions confirmed metastatic disease -for which the patient was starting on triple therapy per the PEACE-1 trial. The PSA level responded appropriately, decreasing from 16.8 to 0.08. Genetic testing was performed and returned negative for any clinically significant mutations.Our patient, diagnosed with peritoneal carcinomatosis during planned RALP, highlights the importance for vigilant laparoscopic exam prior to this prostatectomy. Multidisciplinary discussion is crucial for individualized and optimal treatment planning.